Pelaksanaan Supervisi Pendidikan dalam Mengatasi Permasalahan Guru untuk Meningkatkan Kualitas Pembelajaran - Nilta Rafika; Jamilus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational supervision is a crucial strategy for improving the quality of learning through teacher coaching and mentoring. However, its implementation still faces several challenges, such as a lack of pedagogical competence, a lack of diversity in teaching methods, and a lack of evaluation. This results in suboptimal classroom learning. Therefore, this study aims to examine the application of educational supervision to address various obstacles experienced by teachers and improve the quality of learning. This study employed a literature study approach, utilizing relevant books and scientific articles as sources. Data collection techniques included searching, reviewing, and analyzing literature related to educational supervision and teacher performance. The data obtained were then analyzed descriptively to gain a deeper understanding of the role of supervision in education. These findings demonstrate that structured, systematic, and continuous implementation of educational supervision can help teachers improve the learning process, including planning, implementation, and evaluation. Furthermore, supervision contributes to improving teacher professionalism through the provision of valuable guidance and feedback. So with this, effective educational supervision can be the main solution in overcoming several obstacles, teacher problems as well as improving the quality of learning as a whole.